BUDGET ANALYSIS AS ONE OF THE PLANNING TOOLS AND PRODUCTION CONTROL - Railis, Hendra (Yayasan Education and Social Center, 2022)
A developing company must have a goal so that activities within the company can achieve these goals. It is necessary to have a plan accompanied by effective control. One tool that can meet the planning and control needs is a budget because the budget is formal and systematic rather than the exercise of management responsibilities in planning, coordination, and oversight. This study aims to determine the role of the budget as a means of planning and controlling production and to find out the application of the budget to the